Tingkat Pengetahuan Dagusibu Obat Pada Mahasiswa Farmasi Fakultas Kedokteran Universitas Mataram Tahun 2020 - Intan Ningtyas Sariasih (Faculty of Medicine Universitas Mataram, 2021)
Currently, many health problems occur due to the lack of community knowledge and understanding regarding the procedures for using and managing drugs. This led the Indonesian Pharmacists Association (IAI) to design a program called DaGuSiBu (Get-Use-Save-Dispose). This program is vital for the community and pharmacy students as it is related to its future role for drug information service provider. This study aims to determine the knowledge level of DaGuSiBu in pharmacy students in Faculty of Medicine, University of Mataram. This study harnessed the observational research design with a cross sectional approach. It was conducted in the Pharmacy Study Program, Faculty of Medicine, University of Mataram from February to March 2021, with a sample size of 160 pharmacy students class of 2017 to 2020. Data obtained by distributing online questionnaires that have been tested for validity and reliability. In the aspect of getting medicine, the knowledge level of the students are 20% good, 40% sufficient, and 40% less. In the aspect of using medicine, it has a good knowledge level of 42.8%; 14.3% sufficient; and 42.8% less. In the aspect of storing medicine, the knowledge level was only in the sufficient and insufficient categories of 37.5% and 62.5%. Moreover, in the aspect of disposing of drugs, the knowledge level of the respondents was evenly distributed in the three categories with a value of 33.3%. From the results, it can be concluded that the knowledge level of students varies in 4 aspects, getting, using, storing and disposing of drug.